Санаторно-курортная реабилитация беременных с варикозной болезнью - Жарких, А. В.; Шапран, Н. Ф.; Сюсюка, В. Г.; Сытникова, М. Н.; Нечухаева, И. А.; Жаркіх, Анатолій Васильович; Сюсюка, Володимир Григорович (My University, 2011)
Summary: According to the results of the study, an earlier improvement of general state and reduce of clinical signs of varicose veins in women received proposed complex treatment (magnetic therapy of the lower extremities and sauna therapy in the infrared heat chamber) was stated.